Improving antitumor efficacy via combinatorial regimens of oncolytic virotherapy - Bin Zhang; Ping Cheng (Molecular Cancer, 2020)
Abstract As a promising therapeutic strategy, oncolytic virotherapy has shown potent anticancer efficacy in numerous pre-clinical and clinical trials. Oncolytic viruses have the capacity for conditional-replication within carcinoma cells leading to cell death via multiple mechanisms, including direct lysis of neoplasms, induction of immunogenic cell death, and elicitation of innate and adaptive immunity. In addition, these viruses can be engineered to express cytokines or chemokines to alter tumor microenvironments. Combination of oncolytic virotherapy with other antitumor therapeutic modalities, such as chemotherapy and radiation therapy as well as cancer immunotherapy can be used to target a wider range of tumors and promote therapeutic efficacy. In this review, we outline the basic biological characteristics of oncolytic viruses and the underlying mechanisms that support their use as promising antitumor drugs. We also describe the enhanced efficacy attributed to virotherapy combined with other drugs for the treatment of cancer.